Uji Pemberian Pupuk Organik Cair Fermentasi Daun Gamal terhadap Pertumbuhan Tanaman Sawi (Brassica juncea L.) sebagai Panduan Lembar Kerja Mahasiswa - Taufik Taufik; Iwan Doddy Dharmawibawa; Masiah Masiah (Bioscientist : Jurnal Ilmiah Biologi, 2023)
Liquid organic fertilizer from gamal leaves contains the nutrients N, P, K, Ca and Mg which are useful in plant growth and vegetative development. This research aims to determine the effect of the best dose of gamal leaf liquid organic fertilizer in increasing the growth of mustard greens (Brassica juncea L.). This type of research is a pure experiment using a Completely Randomized Design (CRD), which consists of 5 dose treatments, namely P0 0 ml/l water, P1 30 ml/l water, P2 60 ml/l water, P3 90 ml/l water, and P4 130 ml/l water. Each treatment was repeated 5 times. The parameters observed were plant height, number of leaves, and leaf width. Next, the data was analyzed using One Way ANOVA 5%. The results of the research showed that the best dose of gamal leaf liquid organic fertilizer was in the 130 ml/l treatment, namely the highest plant height was 21.50 cm, the largest number of leaves was 11.8, and the largest leaf width was 10.20 cm. The significant value of the 5% ANOVA test results is 0.000. There is a significant value, namely P < 0.05, so gamal leaf liquid fertilizer has a significant effect on each dose of gamal leaf liquid fertilizer on the vegetative growth of mustard greens. The results of the validation analysis of Student Worksheets (LKM) showed that from the three expert validators, an average validation result of 82% was obtained with very good qualifications, and was declared suitable for use as a LKM guide in plant physiology courses.